Pendampingan Digitalisasi Administrasi Berbasis Komputer Pada Koperasi Ar-Rohmah Wal Barokah Sebagai Upaya Peningkatan Efisiensi Dan Akuntabilitas - Lubna, Surotul (At Taawun Bangun Bangsa, 2025)
Ar-rahmah Wal Barokah Savings and Loan Cooperative is a village-level cooperative under the supervision of the Pasuruan Regency Cooperative Office, with its secretariat located on Jl. Sili Gg. Anggrek, Manaruwi Hamlet, Bangil District, Pasuruan Regency, East Java Province. Prior to the assistance program, the cooperative relied on manual record-keeping, which led to difficulties in retrieving archives and delays in reporting. This community service program aims to enhance accountability and administrative efficiency through the implementation of a computer-based digital system. The study employed a participatory approach with descriptive qualitative analysis. Data were collected through observation, interviews, and documentation. The program was carried out in stages, including basic computer training such as Microsoft Word and Microsoft Excel, as well as intensive assistance in implementing a digital archiving system. The results indicate significant improvements in three key aspects: report preparation speed, accuracy of administrative records, and managerial independence in administrative management. Overall, this program contributes to advancing digital transformation toward a more efficient, accurate, and sustainable administrative system while strengthening the values of trustworthiness and accountability in Islamic financial management.